2010
DOI: 10.1037/a0020356
|View full text |Cite
|
Sign up to set email alerts
|

Loss of visual working memory within seconds: The combined use of refreshable and non-refreshable features.

Abstract: We re-examine the role of time in the loss of information from working memory, the limited information accessible for cognitive tasks. The controversial issue of whether working memory deteriorates over time was investigated using arrays of unconventional visual characters. Each array was followed by a post-perceptual mask, a variable retention interval (RI), and a recognition probe character. Dramatic forgetting across an unfilled RI of up to 6 s was observed. Adding a distracting task during the RI (repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
194
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(224 citation statements)
references
References 62 publications
24
194
4
2
Order By: Relevance
“…Correct rejections (i.e., correctly responding that there was no change) were analyzed by performing an analysis of variance on these percentages with RI duration (1,500 ms, 3,000 ms, or 6,000 ms) and presence of secondary task (no-task vs. parity) as within-subject factors. Like Ricker and Cowan (2010), we observed a significant effect of adding a secondary task, F(1, 26) ϭ 4.97, p Ͻ .05, p 2 ϭ .16, and a significant effect of the duration of RI, F(2, 52) ϭ 10.41, p Ͻ .001, p 2 ϭ .29, with no interaction (F Ͻ 1). Importantly, as we expected, a planned comparison showed that fonts were inevitably lost over time, even when attention was available for refreshing, as demonstrated by the significant effect of RI duration when there was no concurrent task, F(2, 26) ϭ 7.53, p Ͻ .01, with 84%, 70%, and 68% of observed correct rejections for delays of 1,500 ms, 3,000 ms, and 6,000 ms, respectively.…”
Section: Resultssupporting
confidence: 65%
“…Correct rejections (i.e., correctly responding that there was no change) were analyzed by performing an analysis of variance on these percentages with RI duration (1,500 ms, 3,000 ms, or 6,000 ms) and presence of secondary task (no-task vs. parity) as within-subject factors. Like Ricker and Cowan (2010), we observed a significant effect of adding a secondary task, F(1, 26) ϭ 4.97, p Ͻ .05, p 2 ϭ .16, and a significant effect of the duration of RI, F(2, 52) ϭ 10.41, p Ͻ .001, p 2 ϭ .29, with no interaction (F Ͻ 1). Importantly, as we expected, a planned comparison showed that fonts were inevitably lost over time, even when attention was available for refreshing, as demonstrated by the significant effect of RI duration when there was no concurrent task, F(2, 26) ϭ 7.53, p Ͻ .01, with 84%, 70%, and 68% of observed correct rejections for delays of 1,500 ms, 3,000 ms, and 6,000 ms, respectively.…”
Section: Resultssupporting
confidence: 65%
“…Hence, at least for verbal memoranda, whether or not memory declines over a filled RI depends on the variability of distractor processing (see Figure 7). At the same time, some studies using visual or spatial memoranda have found that extending the duration of the RI impairs memory even in the absence of a concurrent processing task (B3; Lilienthal, Hale, & Myerson, 2014;Mercer & McKeown, 2014;Ricker & Cowan, 2010).…”
Section: Round B: Retention Interval and Distractor Processingmentioning
confidence: 99%
“…First, there is strong evidence that at least verbal contents of working memory do not decay (Lewandowsky et al, 2009;Oberauer & Lewandowsky, 2013, 2014. Second, findings that are often cited in support of decay for non-verbal materials -a modest decline of accuracy over several seconds -imply a decay rate much too slow for clearing out working memory at the pace at which our stream of consciousness progresses (McKeown & Mercer, 2012;Mercer & Duffy, 2015;Mercer & McKeown, 2014;Ricker & Cowan, 2010;Ricker, Spiegel, & Cowan, 2014;Zhang & Luck, 2009). Working memory could not function as well as it does without removing outdated information, and the present experiments confirm a role for removal of distractors in keeping working memory working.…”
Section: Distractor Removalmentioning
confidence: 99%